THE PHENOMENON OF HISTORICAL MEMORY IN THE CONTEXT OF THE GENESIS OF HISTORICAL METHODOLOGY - Horban, Olexandr; Martych, Ruslana (Skhid, 2020)
The article analyzes the phenomenon of historical memory and approaches to its study in contemporary scientific discourse. It is stated that its emergence is associated with methodo-logical transformations in the historical science of the last two centuries. Initially, in the course of theoretical research, historical memory was understood as a way of reconstructing the past, when an ethnos or a separate social group builds an image of the past to please the present. As a result of the crisis of traditional historiography, caused by the postmodern criticism of metanarratives, a re-actualization of historical memory occurs. In practice, this occurs in the form of mass commemorations, museumification of common and individual historical heritage, and the creation of an infrastructure for memorial tourism. Historical memory reveals its capabilities to form person’s identity and life guidelines, rooted in the fundamental and universal function of human memory. An important feature of the contemporary research situation is that the rise of historical memory occurs in a crisis of the idea of objectivity and faith in the future. The current stage in the development of historical consciousness gives a new characteristic associated with the general nature of changes concerning various layers and forms of memory, as well as with the collapse of world history and structural changes in historical representations.